The magnetic characteristics of Galactic OB stars from the MiMeS survey of magnetism in massive stars. Issue Volume 9:Issue S302(2013) (7th August 2014) - Wade, G. A.; Grunhut, J.; Alecian, E.; Neiner, C.; Aurière, M.; Bohlender, D. A.; David-Uraz, A.; Folsom, C.; Henrichs, H. F.; Kochukhov, O.; Mathis, S.; Owocki, S.; et al.
Abstract: The Magnetism in Massive Stars (MiMeS) project represents the largest systematic survey of stellar magnetism ever undertaken. Based on a sample of over 550 Galactic B and O-type stars, the MiMeS project has derived the basic characteristics of magnetism in hot, massive stars. Herein we report preliminary results.